2020
DOI: 10.1371/journal.pone.0228388
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of amphenicol resistance in Escherichia coli isolated from pigs in mainland China from 2000 to 2018: A systematic review and meta-analysis

Abstract: BackgroundAmphenicols have been widely used in the pig industry in China, leading to varying degrees of drug resistance. MethodsThe systematic review was performed according to PRISMA (Preferred Reported Items for Systematic Reviews and Meta-Analysis) recommendations on studies investigating the prevalence of amphenicol-resistant Escherichia coli (E. coli) isolated from pig in mainland China from 2000 to 2018, a random-effects model was selected, then followed by meta-analysis. ResultsA total of 103 articles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Amphenicols present a broad-spectrum inhibitory effect on both gram-positive and -negative bacteria but are particularly effective against the latter. The severe levels of resistance to amphiphenicles may be attributable to spread or abuse in the animal industry, which may have increased selective pressure on E. coli [ 52 ]. The antibiotic resistance profiles observed for the two EPEC strains showed high variability, confirming the importance of the considerable polymorphism of genes encoding for this virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…Amphenicols present a broad-spectrum inhibitory effect on both gram-positive and -negative bacteria but are particularly effective against the latter. The severe levels of resistance to amphiphenicles may be attributable to spread or abuse in the animal industry, which may have increased selective pressure on E. coli [ 52 ]. The antibiotic resistance profiles observed for the two EPEC strains showed high variability, confirming the importance of the considerable polymorphism of genes encoding for this virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…An issue that can be underlined refers to the obviousness that CAP is a well-studied protein synthesis inhibitor, representing the basis for obtaining derived compounds with similar benefits and minimal side effects [ 10 ]. Thus, TAP and FF are structural analogs of CAP; TAP is a second generation CAP derivative with a methane-sulfonyl group instead of para-nitro group and FF is a fluorinated derivative of TAP (third generation), in which the hydroxyl group at C3 is replaced with fluorine [ 11 ]. Due to the fact that TAP and FF are less toxic than CAP, but exhibit analogue antibacterial mechanisms, they successfully replaced CAP for veterinary use.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the emergence of multidrug-resistant bacteria, it has been difficult to treat related bacterial infections in a clinical setting. Studies have shown that amidol antibiotics have a certain inhibitory effect on multidrug-resistant bacteria . Amidol antibiotics, which are also known as chloramphenicol antibiotics, are a class of broad-spectrum antibiotics that primarily include (−)-chloramphenicol, (−)-azidamphenicol, (+)-thiamphenicol, and (+)-florfenicol.…”
Section: Introductionmentioning
confidence: 99%